Criminal associations aimed at committing environmental crimes and aggravating circumstances applicable to the association - Giulio Monferini (Lexambiente, 2020)
This report concerns environmental criminal organizations and the system of aggravating circumstances of the associative crime, committed to the commission of crimes against the environment. A criminal association is aggravated if it has the purpose of committing environmental crimes. Ordinary and mafia-type criminal organizations are analyzed in the different possible configurations for the commission of crimes against the environment. It is explored in which cases it is possible to contest the aggravating circumstance even if the crimes that are the purpose of the association have not yet been committed. The second part of the study concerns the further aggravating circumstance, properly defined environmental aggravating, and its compatibility with the criminal organization, when the association in its action violates the environmental protection rules of various kinds, both criminal and administrative. Then it was asked whether it is possible to charge the so-called environmental aggravating circumstance also to a criminal association dedicated to environmental crimes